THE ROLE OF ANTI MULLERIAN HORMONE (AMH) LEVELS AS PREDICTIVE AND DIAGNOSTIC BIOMARKER OF AGE AT MENOPAUSE AMONG INFERTILE SUDANESE WOMEN (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Infertility is a global health problem with an increasing incidence rate among Sudanese women. The study aimed to compare serum anti-mullerian hormone (AMH), folic stimulating hormone (FSH) and luteinizing hormone (LH) between primary infertility and secondary infertility. Furthermore, also to study the effect of woman's age on these hormones. The study was carried out in Khartoum State, Sudan during the period from January to March 2017. A cross sectional hospital included 260 infertile women [169 with primary infertility (mean age 32.7 ± 7.26 years) and 91 with secondary infertility (mean age 35.02 ± 6.25 years). Three ml of venous blood were collected in plain container and serum were obtained by centrifugation, all serum samples were analyzed for AMH, FSH and LH concentration using ELISA techniques. The results were showed significant difference in LH andAMH between primary infertility and secondary  infertility  (P value  =  0.017,  0.001 respectively) and insignificant differences in FSH between them  (P value  = 0.606). Furthermore, the serum AMH level decreased in elder ages (P value = 0.000; r = - 0.4564) and increased of FSH level (P value = 0.001; r = - 0.199). In addition, the serum FSH levels increase in elder ages (P value = 0.001: r = -0.2036). In conclusion, the results of this study showed that hormones play a crucial role in diagnosis infertile women and serum AMH concentration has created more promising results to predicting age at menopause.